INSURANCE AND ACTUARIAL OLYMPIAD TO INCREASE THE LITERACY OF SMA/SMK/MA STUDENTS IN INDONESIA - Lie, Antonius Anton; Indra, I Made; Novika, Fanny; Awaloeddin, Mulawarman; Fandayani, Enno Karina (Yayasan Education and Social Center, 2024)
Insurance and Actuarial are interrelated disciplines. However, the level of public literacy in these two fields still needs to be higher, even though both have the potential to create economic stability in Indonesia. Therefore, increasing insurance and actuarial literacy in society is critical. This service activity allows the community, especially SMA/SMK/MA students, to increase insurance literacy through participation in Olympic activities. A total of 256 participants competed in the preliminary round, of which 68 advanced to the semifinal round, and finally, only 12 in the insurance and actuarial fields advanced to the final round. The preliminary and final rounds were held offline, while the final round was held online. In the final round, the finalists answered questions from judges who were experts in the insurance and actuarial fields and provided explanations of their answers to the public via the YouTube channel. This Olympic activity received a good response from practitioners in the insurance sector, who were impressed by the finalists' ability to provide excellent answers